Stimulation of the metal doping process of nanoporous carbon material by laser irradiation - Budzulyak, I.M.; Yablon, L.S.; Khemii, M.M.; Kotsyubynsky, V.O.; Rachiy, B.I.; Ilnytskyi, R.V.; Kryvulych, R.I. (Physics and Chemistry of Solid State, 2023)
It has been established that the doping of activated carbon material with chromium and manganese increases the specific capacitance of storage devices based on the charge-discharge mechanism of a double electric layer (DEL) by 70 % and leads to a decrease in their internal resistance by 30-35 %. The main reason for this rise is the transformation of the electron energy spectrum due to an increase in the density of electronic states, as a result of which a much larger number of electrolyte ions (primarily positive ones) participate in the formation of DEL and cause an increase in the specific capacitance of these devices. It has been shown that laser irradiation stimulates the metal penetration into the bulk of carbon material.